Identifikasi Lokasi Pemusatan Fasilitas Rumah Sakit Kota di Surakarta - Feri Karlina Pangestuti; Andareswari, Novi; Ulya, Ayu Fitriatul (CV. Gio Architect, 2024)
Health is the optimal general state of one's body, mind, and spirit. Someone can do an activity because there is a healthy body so in general everyone always tries to stay healthy. The availability and convenience of health facilities is one of the efforts made by the government to improve the quality of public health. The purpose of this study with the Mean center method and Density estimation analysis with Heatmap, is to gain a better understanding of data distribution patterns. The Mean center method is used to determine the central point of distribution of data which can then be used as a reference to analyze and understand further distribution patterns. From this analysis it can be concluded that the Mean center method can help in identifying the center point or midpoint in the Surakarta area, describing the ideal location in Surakarta City, this method allows geographical representation of the center point using geographical coordinates such as latitude and longtitude which can then provide an easy understanding of the relative location of the center point of the hospital to other hospitals in the region. The results of the Mean center show that the center point of the hospital is located in Kelurahan Kestalan, Kecamatan, Banjarsari Surakarta City. Density estimation results in 3 (three) concentration clusters in Surakarta City. This helps local governments in plans to add health facilities, because of the gap in the northern, central and southern regions.